Explaining public support for violence against politicians during conflict: Evidence from a panel study in Israel. (May 2021) - Elad-Strenger, Julia; Hall, Brian J; Hobfoll, Stevan E; Canetti, Daphna
What drives citizens' support for violence against domestic political actors? Despite its potentially devastating consequences, there is surprisingly little research on the antecedents of this unique form of political violence. Building upon recent insights on the psychological implications of exposure to conflict on support for political violence, we examined the motivations underlying public support for violence against politicians in the context of protracted conflict. Using a two-wave panel design among Jewish-Israelis, we examined the interactive effects of conflict-induced perceived threat, psychological distress, and political orientation on support for violence against politicians. Consistent with previous findings on the psychological implications of conflict, our findings suggest that conflict-induced threat perceptions play an important role in predicting support for violence against politicians. Nevertheless, our findings point to important boundary conditions to these effects: the strength of the relationship between perceived threat and attitudes towards political violence is qualified by the level of chronic conflict-related psychological distress, and the direction of the effects of perceived threat is qualified by individuals' self-placement on the left-right continuum. More specifically, we found that perceived threat increased rightists' support and decreases leftists' support for violence against politicians, only under high, but not low, conflict-related psychological distress. The main conclusion of this study is that support for violence against politicians can be seen as an ideology-driven protective strategy against the negative psychological implications of exposure to violent conflict. By pointing to the importance of understanding the interactive role of psychological and political factors in determining public support for such acts, our findings therefore contribute to the understanding of a relatively understudied phenomenon with potentially catastrophic effects on political stability.